Better glycaemic control with BioChaperone glargine lispro co‐formulation than with insulin lispro Mix25 or separate glargine and lispro administrations after a test meal in people with type 2 diabetes. Issue 7 (8th April 2019) - Meiffren, Grégory; Herbrand, Theresa; Anastassiadis, Ernestos; Klein, Oliver; DeVries, J. Hans; Heise, Tim; Alluis, Bertrand; Mégret, Claire; Gaudier, Martin; Soula, Olivier; Plum‐Mörschel, Leona
Abstract : Because of its physico‐chemical properties, insulin glargine is usually not mixable with rapid insulins. BioChaperone BC147 is a polyanionic amphiphilic polymer, solubilizing insulin glargine at neutral pH, and thus enabling stable glargine formulation with fast‐acting insulin lispro (BioChaperone glargine lispro co‐formulation [BC Combo]). We investigated pharmacokinetic (PK) endpoints and postprandial glucose (PPG) control after administration of BC Combo (75% insulin glargine, 25% insulin lispro), insulin lispro Mix25 (LMix) and separate injections of insulins glargine (75% total dose) and lispro (25% total dose [G + L]) immediately before ingestion of a mixed meal in people with type 2 diabetes mellitus (T2DM), using a randomized, double‐blind, double‐dummy crossover study design. Participants received individualized bolus doses (mean 0.62 U/kg) of BC Combo, LMix or G + L, together with a solid mixed meal (610 kcal, 50% carbohydrate, 30% fat, 20% protein). Insulin dosages were kept constant for each study day. Thirty‐nine participants with T2DM (mean ± SD age and glycated haemoglobin 60.8 ± 7.5 years and 64 ± 6 mmol/mol, respectively) were randomized. BC Combo improved the predefined primary endpoint, early PPG control, compared to LMix (incremental area under the blood glucose concentration–time curve from 0 to 2 hours after the meal [ΔAUCBG, 0–2h ] reduction of 18%; P = 0.0009) and G + L (ΔAUCBG, 0–2h reduction of 10%; P = 0.0450). The number of mealtime hypoglycaemic episodes per participant was lower with BC Combo (22 episodes in 14 participants) compared to LMix (43 episodes in 20 participants; P = 0.0028), but not significantly different from G + L (28 episodes in 19 participants; P = 0.2523). BC Combo demonstrated superior early PPG control with fewer hypoglycaemic episodes compared to LMix and superior early PPG control compared to separate G + L administrations.